Electrochemical and compositional characterization of solid interphase layers in an interface-modified solid-state Li–sulfur battery. Issue 32 (30th July 2020) - Pervez, Syed Atif; Vinayan, Bhaghavathi P.; Cambaz, Musa Ali; Melinte, Georgian; Diemant, Thomas; Braun, Tobias; Karkera, Guruprakash; Behm, R. Jürgen; Fichtner, M.
Abstract : Formation of nano-sized interphase layers, containing organic and inorganic species, in an interface modified Li–sulfur solid-state battery. Abstract : The Li + transport kinetics at the solid–solid electrode|electrolyte interfaces are crucial for the stable and durable performance of solid-state batteries (SSBs). A poor interface due to mechanical problems and/or (electro-)chemical instabilities will curtail the performance of such batteries. Herein, we present a detailed study on the interfaces of a lithium–sulfur (Li–S) SSB with a Li anode, Li–garnet (LLZO) solid electrolyte (SE), and a sulfur–carbon composite as the cathode. Interlayer gels based on ionic liquids were introduced to improve the interfacial properties of the system. For Li symmetric cells, the strategy resulted in a decrease in cell resistance by about a factor of five and stable voltage profiles with low overpotentials (∼300 mV at 0.4 mA cm −2 after >450 hours). Furthermore, the LLZO SE efficiently blocked the polysulfide shuttle to the Li anode. Due to the advantageous features of the design, good electrochemical performance was obtained, where the Li–S SSB delivered an initial discharge capacity of ca. 1360 mA h gsulfur −1 and a discharge capacity of ca. 570 mA h gsulfur −1 after 100 cycles. Detailed electrochemical and compositional characterization of the interphase layers was performed at the Li anode and sulfur cathode interfaces through X-ray photoelectron spectroscopy (XPS), applying depth-profiling techniques, and scanning transmission electron microscopy (STEM). The results revealed the presence of interphase nano-layers with varying thicknesses on the LLZO surface which contained organic and inorganic species.